Intelligent system of management and providing dairy cattle production effectiveness on a smart farm - Yu. A. Ivanov; V. K. Skorkin; P. I. Gridnev; D. K. Larkin (Аграрная наука Евро-Северо-Востока, 2019)
Russia is one of the largest milk producing countries in the world (over 30.0 million tons per year), but in some parameters western countries predominate.  In our country the cost of feed per 1 centner of products exceeds 1.3 times, labor and electricity consumption 2.5-3.5 times, cow milk production is 1.6-2.2 times lower. The cause of low indexes lies in outdated technologies such as tie-up housing, a significant proportion of manual labor, low feed quality and skills of the staff. The implementation of modern livestock keeping technologies, automated machinery of a new generation, intelligent system of technological processes control will result in a leap forward in dairy farming by establishing smart farms. Smart farms with intelligent control of technological processes will lead to significant increase in production efficiency. The smart farm control is carried out through a number of automated units. The human role is reduced to the general control and industrial complex management. The final part of this system is an automatic block of the company activities results analysis and management decisions correcting. Milk quality is also influenced by the somatic cells content, the level of which reaches 18-29%. The laboratory created by the institute and the computer developed program allow to carry out more than 15-20 thousand of milk individual samples’ analyses with evaluation of the main milk quality indicators and physiological condition of animals. The created system of smart dairy farms intelligent control with developed computer programs will reduce the cost of a cattle stall to 400,000 rubles, the cost of 1 kg of milk - to 20 rubles. At the same time, the production profitability will be 45-50%, the economic use of cows - up to 4-5 lactations.